PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SICEPAT EKSPRES INDONESIA CABANG SUNGAI PENUH - Mauledy Ahmad; Zefri Efdison; Edia Satria; Yolla Ramadani (Institut Agama Islam Negeri Kerinci, 2023)
Purpose: This study aims to examine the effect of workload and compensation on employee productivity at PT.SiCepat Ekspres Indonesia Sungai Penuh branch. Design/Methodology/Research Approach: This study uses a causality quantitative approach. The sample in this study were employees of PT.SiCepat Ekspres Indonesia Branch of Sungai Lilin City, totaling 33 respondents. Data was collected using a questionnaire, while the data analysis technique used was multiple linear regression analysis. Findings: there is an effect of Workload, and Compensation on Work Productivity with the magnitude of the influence of 70.7%. Research Implications: The results of this study prove that a high workload tends to reduce work productivity, whereas high compensation tends to increase employee productivity.